1975
DOI: 10.1111/j.1432-1033.1975.tb04148.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl‐Coenzyme‐A Carboxylase in Cultured Hepatocytes

Abstract: Studies were made on the content, synthesis and degradation of acetyl-coenzyme-A carboxylase in JTC-25 . P3 cells, hepatocytes which can be maintained in a protein-free and lipid-free chemically defined medium. The addition of corn oil or fatty acid to the medium resulted in a decrease in the activity level of the enzyme without impairing the viability of cells. All the fatty acids tested exhibited this effect, although linoleic acid and oleic acid were more effective than palmitic acid, stearic acid and arach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

1975
1975
1986
1986

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…, (Nakanishi & Numa, 1971). The half-life of acetyl-CoA carboxylase as determined in primary hepatocyte cultures in the present study (39 h) was higher than that observed in an established hepatocyte cell line [28h (Kitajima et al, 1975)]. However, it was smaller than the half-life in intact rats [48 h (Majerus & Kilburn, 1969); 59h (Nakanishi & Numa, 1970)].…”
Section: Results Tant Which Wascontrasting
confidence: 50%
“…, (Nakanishi & Numa, 1971). The half-life of acetyl-CoA carboxylase as determined in primary hepatocyte cultures in the present study (39 h) was higher than that observed in an established hepatocyte cell line [28h (Kitajima et al, 1975)]. However, it was smaller than the half-life in intact rats [48 h (Majerus & Kilburn, 1969); 59h (Nakanishi & Numa, 1970)].…”
Section: Results Tant Which Wascontrasting
confidence: 50%
“…The procedures used were ammonium sulfate fractionation of the soluble supernatant fraction, calcium phosphate gel adsorption and elution, a second ammonium sulfate fractionation, DEAE-cellulose chromatography, and Sepharose 2 B chromatography. Thc final enzyme preparations exhibited a specific activity of 5-7 U/mg of protein at 37 C. Their homogeneity was ascertained as described previously [18] Beckman SW-65L Ti rotor at 19 "C and 40000 rev./ min for 100 min. In order to confirm that the radioactivity found in the purified enzyme was actually located in its biotinyl prosthetic group, 150 pg of the labelled enzyme (25 500 counts/min) was first heated at 60 "C for 5 min and then digested with 50 pg proteinase K at 37 "C for 24 h in 60 pl0.1 M Tris-C1 buffer pH 7.0.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, isotopic leucine incorporation studies with the use of immunochemical techniques have revealed that the reduction of the enzyme content upon addition of fatty acid to the culture medium can be ascribed to a decrease in the rate of synthesis of the enzyme, while the rate of degradation of the enzyme is not affected by exogenous fatty acid (5). On the basis of these findings, it appears reasonable to assume that the observed decrease in the acetyl-CoA carboxylase content of S. cerevisiae likewise represents a repression of the enzyme.…”
mentioning
confidence: 99%